Intervención del terapista respiratorio en paciente masculino de 27 años con crisis de asma. - Gomez Olvera, Lisbeth Mabel (2022)
Asthma is a pathology that is based on edematization of the lower airway, it becomes a severe risk in certain cases, this disease is self-limiting in pediatric patients and older adults. Among the factors that are evidenced related to asthma and asthmatic crisis, are classified into social, environmental and biological, where allergens, bacteria, viruses, cigarette smoke, exposure to fumes from textile factories, environmental pollution and dust are determined. The signs that can be evidenced are the decrease in systolic blood pressure, in addition to evidencing the patient tachypneic, tachycardic, and severe respiratory distress, sometimes patients show cyanosis in chronic cases, in addition there is evidence of inability to speak. In the clinical case study based on a 27-year-old male patient with asthmatic crisis, the general objective of which was to analyze the procedures performed by the respiratory therapist, in the interventions performed by the professional, oxygen therapy was applied to control desaturation and administration of medication by nebulization and control of vital signs, in addition to constant monitoring of the patient with asthmatic crisis. In conclusion, it was possible to determine the severity of the asthmatic crisis in a 27-year-old male patient, using complementary examinations and analyzing the interventions applied.